What do library users really want? The application of a market research tool. - Lock, Selena A. (Cranfield University, 2006)
In order to provide services that the users desire you must first evaluate exactly what users (and potential users) want from the library. This paper discusses how Cranfield University set out to do this in order to shape the future strategy of the library in line with both user needs and internal goals. The LibQUAL+ library survey tool was used to assess what the users want from the library service. The findings from Cranfield and SCONUL are presented with a view to informing library managers of the potential needs of their users.
For publication in the SCONUL Briefing Paper on Marketing.
Keywords: libraries; user surveys; performance measurement; market research; LibQUAL+; questionnaire